Hospital readmission and 30‐day mortality after surgery for oral cavity cancer: Analysis of 21, 681 cases. (9th September 2015) - Luryi, Alexander L.; Chen, Michelle M.; Mehra, Saral; Roman, Sanziana A.; Sosa, Julie A.; Judson, Benjamin L.
Abstract: Background: Oral cavity squamous cell cancer (SCC) is treated primarily with surgery. Rates of 30‐day hospital readmission and mortality after surgery for oral cavity SCC are unknown. Methods: We conducted a retrospective analysis of postoperative 30‐day unplanned readmission and mortality in patients with oral cavity SCC in the National Cancer Data Base (NCDB). Results: Among 21, 681 cases, the 30‐day unplanned readmission rate was 3.2%, and the 30‐day mortality rate was 1.0%. Male sex (odds ratio [OR] = 1.23; p = .02), stage T3 (OR = 1.55; p = .007), or T4 (OR = 1.52; p = .002), and neck dissection (OR = 1.37; p = .04) were independently associated with readmission. Age 76 to 85 years (OR = 4.80; p < .001), age >85 years (OR = 10.24; p < .001), comorbidity index ≥1 (OR = 2.31; p < .001), and stage T3 (OR = 3.02; p < .001) or T4 (OR = 3.24; p < .001) were associated with 30‐day mortality. Conclusion: Interventions aimed at decreasing hospital readmissions should target high‐risk patients identified here. Factors associated with 30‐day mortality reflect risk factors for overall mortality. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E221–E226, 2016